Visible-Transparent Luminescent Solar Concentrators Based on Carbon Nanodots in the Siloxane Matrix with Ultrahigh Quantum Yields and Optical Transparency at High-Loading Contents - Talite, Maria Jessabel; Huang, Hsiu-Ying; Cai, Kun-Bin; Co, King Chester Capinig; Santoso, Phoa Adelina Cynthia; Chang, Sheng-Hsiung; Chou, Wu-Ching; Yuan, Chi-Tsu (My University, 2020)
Visible-transparent luminescent solar concentrators (VT-LSCs) can be integrated with solar cells for designing solar glasses. Recently, rare-earth complexes, semiconductor nanocrystals, and carbon nanodots (CNDs) have been applied in developing VT-LSCs. However, several challenges still existed, such as quantum yields (QYs) at high-loading contents, scattering/reabsorption losses, and stability. Here, highly luminescent and visible-transparent composites based on organosilane-functionalized CNDs (Si-CNDs) cross-linked in the siloxane matrix were prepared. The composites with a high-loading content (similar to 10 wt %) possess ultrahigh QYs of similar to 94% due to surface passivation, cross-linking-enhanced emission, and negligible inter-CND energy transfer. Moreover, they still appear exceptionally transparent and, thus, are suitable for VT-LSCs. Eco-friendly VT-LSCs without colored tinting were fabricated, yielding high internal and external quantum efficiencies of similar to 66% and similar to 3.9%. Our demonstration would pave a bright way for the utilization of eco-friendly VT-LSCs in solar glasses.